2021
DOI: 10.21203/rs.3.rs-625958/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Addition of Clinoptilolite In The Diet Reduces Uterine PMN Leukocytes And Open Days In Multiparous Lactating Dairy Cows Managed In A Mountain Tropical Pasture-Based System

Abstract: This study was aimed to assess the effect of adding clinoptilolite in the diet on uterine health and reproductive performance in multiparous lactating dairy cows managed in a tropical pasture-based system above 2500 meters of altitude. Seventy-seven multiparous Holstein crossbred cows were allocated randomly into two groups: clinoptilolite supplemented cows (CLG, n = 42) and non-supplemented cows as control (CG, n = 35). Cows from CLG were supplemented with clinoptilolite from 30 days (50 g/cow/day) before to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Numerous studies have shown that orally administered zeolite has positive effects on improving metabolic and reproductive indicators (Crookenden et al, 2020;Garzón et al, 2017;Franklin et al, 2021;Khachlouf et al, 2018). Furthermore, the antibacterial effects of zeolite have been demonstrated in calf diarrhoea cases (W u et al, 2013).…”
Section: Total Puerperium Evaluationmentioning
confidence: 99%
“…Numerous studies have shown that orally administered zeolite has positive effects on improving metabolic and reproductive indicators (Crookenden et al, 2020;Garzón et al, 2017;Franklin et al, 2021;Khachlouf et al, 2018). Furthermore, the antibacterial effects of zeolite have been demonstrated in calf diarrhoea cases (W u et al, 2013).…”
Section: Total Puerperium Evaluationmentioning
confidence: 99%